2019
DOI: 10.1146/annurev-polisci-050317-070912
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the “Sinew of War”: The Political Economy of Security as a Subfield

Abstract: Since at least Cicero, we have known that “money is the sinew of war.” Is it possible for a political economy of security (PES) subfield to contribute knowledge beyond Cicero's claim? This article aims to delineate the boundaries of a PES subfield by using the classic “guns versus butter” trade-off to define the existing literature within the subfield. Thinking seriously about this trade-off, including conditions under which a trade-off may not exist, raises a host of questions. The two most direct questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 191 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, it is commonly suggested that ASEAN's perceptions on the linkages between economic security interests have significantly moved away from realist paradigms. ASEAN's continuing emphasis on regional economic cooperation and integration over the past three decades suggests that member states have embraced the liberal ideals of commercial peace (Bearce and Omori, 2005; Goldsmith, 2007; Haftel and Hofmann, 2017; Peou, 2002), albeit arguably, and extended the scope of economic security into non-traditional security issues (Caballero-Anthony, 2018; Peou, 2014).…”
Section: Asean Economic Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is commonly suggested that ASEAN's perceptions on the linkages between economic security interests have significantly moved away from realist paradigms. ASEAN's continuing emphasis on regional economic cooperation and integration over the past three decades suggests that member states have embraced the liberal ideals of commercial peace (Bearce and Omori, 2005; Goldsmith, 2007; Haftel and Hofmann, 2017; Peou, 2002), albeit arguably, and extended the scope of economic security into non-traditional security issues (Caballero-Anthony, 2018; Peou, 2014).…”
Section: Asean Economic Securitymentioning
confidence: 99%
“…Relying on a historical institutional approach, Stubbs and Mitrea (2017) maintain that ASEAN's durability as a regional organization has been enhanced by the timing and nature of changes in the global economy over the past decades. The influx of foreign aid and foreign investment from the 1970s through the early 1990s boosted ASEAN economies with major infrastructure projects, promoting political stability and social progress.…”
Section: Asean Economic Cooperation and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Every dollar spent and allocated to the military could be spent and allocated to the direct satisfaction of basic human needs and the improvement of human and ecological life in general. The enormous ‘opportunity cost’ of military spending is why Yale economists Nordhaus and Tobin (1972) once referred to it as a ‘regrettable expense’ (Poast, 2019: 225). Nearly a decade before his 1961 farewell address and warning of the growing undemocratic influence of the ‘military-industrial-complex’, former NATO Commander and then US President D.D.…”
Section: Introductionmentioning
confidence: 99%